Increased Prevalence of Severe Fever with Thrombocytopenia Syndrome in Eastern China Clustered with Multiple Genotypes and Reasserted Virus during 2010–2015 - Zhifeng Li (Nature Portfolio, 2017)
Abstract Severe fever with thrombocytopenia syndrome (SFTS) is a novel tick-borne viral disease with high mortality. Since January 2010, we have conducted an epidemiological surveillance and etiological study of SFTS in Jiangsu and Anhui provinces. From January 2010 through December 2015, a total of 286 SFTS cases were confirmed in Jiangsu and Anhui provinces with a case fatality rate of 16.1%. The majority of confirmed SFTS cases were distributed in the border area of Jiangsu and Anhui provinces. Our findings suggest that the SFTS prevalence rate rose since 2010 and reached its highest in 2015. Phylogenetic analysis demonstrated that the majority of the SFTSV strains (83.6%) from Jiangsu and Anhui provinces belonged to genotypes A and D. Notably, we identified three strains of SFTSV clustered into the genotype E. This is the first report of the genotype E SFTSV strains in mainland of China. A reassortment between genotype A and D was found in the central region of the endemic areas, where three SFTSV genotypes (A, C and D) were co-circulating.